EFEKTIVITAS KOMBINASI MEDIA ADSORBENT TONGKOL JAGUNG DAN CANGKANG KERANG DENGAN METODE MULTI SOIL LAYERING (MSL) PADA LIMBAH CAIR HOTEL - Okik Hendriyanto Cahyonugroho; Rachmat Yuda Hardiyanto (EnviroUS, 2022)
Liquid waste generated from hotels has the same characteristics as household liquid waste. The characteristics are containing BOD and Ammonia. If the BOD and Ammonia content is disposed of without going through the processing unit, it will cause water pollution. To minimize BOD and Ammonia levels, efforts are needed through the Multi Soil Layering (MSL) process with adsorbent corn cob media, adsorbent clam shell media, or a combination of corn cob and clam shell media. This research is used to find out the effect of the comparison of variations soil and HLR using adsorbent corn cob media, clam shell, or combination to reduce BOD and Ammonia levels. This study uses a continuous system which is carried out with 2 treatment factors, there are soil variations (0:100, 25:75, 50:50, 75:25, 100:0) and HLR variations (100, 250, 500, 750, 1000 L/m2.hari). The best results obtained from this study were BOD removal with a combination of adsorbent corn cob media and adsorbent clam shell media with soil variation of 25:75 at HLR 100 L/m2.day of 86% with a concentration of 4.2 mg/L. Meanwhile, the removal of Ammonia with a combination of adsorbent corn cob media and adsorbent clam shell media with soil variation of 25:75 at HLR 100 L/m2.day of 91.27% with a concentration of 7.86 mg/L.